Sustainable automated carton making factory: How value for money procurement can add value to the Palmal group of Industry and gain competitive advantage. (2019) - Amin, Md Al (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020..